Efficiency and Optimal size of Italian Public Hospitals: Results from Data Envelopment Analysis (Epidemiology, Biostatistics, and Public Health, 2022)
Background: One of the major issues discussed in the literature about hospital efficiency is the impact of hospital size on technical efficiency. Many studies have observed that in some cases, hospital technical inefficiency is correlated with an incorrect size. This paper addresses this topic. In particular, we attempt to identify an optimal size of hospitals in terms of beds.Methods: The study is organized as follow: first, we performed the Data Envelopment Analysis in order to calculate the technical and scale efficiency scores for a sample of 41 Italian public hospitals during the period 2010-2013; second, we investigated the impact of size on hospital efficiency, identifying the magnitudes of input reductions needed to make inefficient public hospitals efficient. Finally, we calculated the most productive scale size for each hospital in the sample. According to these results, through an overall observation, we attempted to identify an optimal size for hospitals in terms of beds.Results: Most of the hospitals were inefficient and most of the inefficiency was the results of the presence of waste in terms of input resources. During the period considered, we found that inputs could be reduced by 22% on average. Economies of scale were found around 200 beds for 20.000 discharges per year.Conclusions: The identification of an optimal size of hospitals in terms of beds still requires further efforts in the literature. However, this study contributes to support hospital managers in resource allocation choices through a quantitative approach.